The Influence of Endorsement and Content Marketing and Brand Trust on Customer Loyalty on the Shopee platform - Rudi Sugianto; Yusuf Yusuf (Interdisciplinary Social Studies, 2026)
Rapid progress in the field of e-commerce in Indonesia has made competition between platforms increasingly fierce, so consumer loyalty is important for business sustainability. Shopee, as a well-known e-commerce platform in Indonesia, has problems in maintaining buyer loyalty when there are so many marketplace choices. This research was created to examine the effects of endorsements, content marketing, and brand trust on consumer loyalty on the Shopee platform. The research method used is quantitative with a survey method. Data was obtained from the distribution of questionnaires to 135 respondents, namely active Shopee users in Cirebon City, who were selected using the purposive sampling technique. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique using the SmartPLS application. The results of the measurement model test show that all constructs have met the requirements for validity and reliability. The results of the structural model analysis indicate that endorsements have a good and important impact on buyer loyalty. Content marketing also shows a good and important impact on buyer loyalty, with the greatest impact compared to other variables. In addition, brand trust has been proven to have a good and important impact on Shopee user loyalty. A determination coefficient (R²) value of 0.575 indicates that endorsement, content marketing, and brand trust may explain shopper loyalty in the moderate group. The findings of this study show that e-commerce user loyalty is influenced by effective digital marketing communication strategies, supported by relevant content and consumer trust levels in brands.